Logging intensity drives variability in carbon stocks in lowland forests in Vietnam - Stas, Suzanne M.; Le, Tinh Cong; Tran, Hieu Dang; Hoang, Thi Thai Hoa; van Kuijk, Marijke; Le, An Van; Ngo, Duc Tung; van Oostrum, Ad; Phillips, Oliver L.; Rutishauser, Ervan; Spracklen, Benedict D.; Tran, Tuyet Thi Anh; et al. (Forest ecology and management, 2020)
•Aboveground carbon was lower in heavily logged forests, mainly of stems ≥60 cm dbh.•SOC in the 0–30 cm top layer stored ~50% of total carbon stocks in logged forests.•Logging intensity was the main factor explaining variability in aboveground carbon.•A new approach to estimate historical logging intensities is presented. Forest degradation in the tropics is generating large carbon (C) emissions. In tropical Asia, logging is the main driver of forest degradation. For effective implementation of REDD+ projects in logged forests in Southeast Asia, the impacts of logging on forest C stocks need to be assessed. Here, we assess C stocks in logged lowland forests in central Vietnam and explore correlations between logging intensity, soil, topography and living aboveground carbon (AGC) stocks. We present an approach to estimate historical logging intensities for the prevalent situation when complete records on logging history are unavailable. Landsat analysis and participatory mapping were used to quantify the density of historical disturbances, used as a proxy of logging intensities in the area. Carbon in AGC, dead wood, belowground carbon (BGC) and soil (SOC) was measured in twenty-four 0.25 ha plots that vary in logging intensity, and data on recent logging, soil properties, elevation and slope were also collected. Heavily logged forests stored only half the amount of AGC of stems ≥10 cm dbh as lightly logged forests, mainly due to a reduction in the number of large (≥60 cm dbh) trees. Carbon in AGC of small trees (5–10 cm dbh), dead wood and BGC comprised only small fractions of total C stocks, while SOC in the topsoil of 0–30 cm depth stored ~50% of total C stocks. Combining logging intensities with soil and topographic data showed that logging intensity was the main factor explaining the variability in AGC. Our research shows large reductions in AGC in medium and heavily logged forests. It highlights the critical importance of conserving big trees to maintain high forest C stocks and accounting for SOC in total C stock estimates.